Heterogeneities of Site-Specific N-Glycosylation in HCC Tumors With Low and High AFP Concentrations - Zhao, Ting; Jia, Li; Li, Jun; Ma, Chen; Wu, Jingyu; Shen, Jiechen; Dang, Liuyi; Zhu, Bojing; Li, Pengfei; Zhi, Yuan; Lan, Rongxia; Xu, Yintai; et al. (Frontiers in Oncology, 2020)
Hepatocellular carcinoma (HCC) is still one of the malignant tumors with high morbidity and mortality in China and worldwide. Although alpha-fetoprotein (AFP) as well as core fucosylated AFP-L3 have been widely used as important biomarkers for HCC diagnosis and evaluation, the AFP level shows a huge variation among HCC patient populations. In addition, the AFP level has also been proved to be associated with pathological grade, progression, and survival of HCC patients. Understanding the intrinsic heterogeneities of HCC associated with AFP levels is essential for the molecular mechanism studies of HCC with different AFP levels as well as for the potential early diagnosis and personalized treatment of HCC with AFP negative. In this study, an integrated N-glycoproteomic and proteomic analysis of low and high AFP levels of HCC tumors was performed to investigate the intrinsic heterogeneities of site-specific glycosylation associated with different AFP levels of HCC. By large-scale profiling and quantifying more than 4,700 intact N-glycopeptides from 20 HCC and 20 paired paracancer samples, we identified many commonly altered site-specific N-glycans from HCC tumors regardless of AFP levels, including decreased modifications by oligo-mannose and sialylated bi-antennary glycans, and increased modifications by bisecting glycans. By relative quantifying the intact N-glycopeptides between low and high AFP tumor groups, the great heterogeneities of site-specific N-glycans between two groups of HCC tumors were also uncovered. We found that several sialylated but not core fucosylated tri-antennary glycans were uniquely increased in low AFP level of HCC tumors, while many core fucosylated bi-antennary or hybrid glycans as well as bisecting glycans were uniquely increased in high AFP tumors. The data provide a valuable resource for future HCC studies regarding the mechanism, heterogeneities and new biomarker discovery.